2017
DOI: 10.1017/s0022029917000644
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in ITIH4, AHSG, ORM1, and CD46 content in milk fat globule membrane proteins of ketotic dairy cows

Abstract: High concentrations of non-esterified fatty acid (NEFA) and β-hydroxybutyrate (BHBA) in cows' blood caused by ketosis are associated with inflammatory states. We hypothesised that ketosis in postparturient dairy cows would result in altered levels on inflammation-related proteins not only in plasma but also in the milk fat globule membranes (MFGM). Thirty cows were selected from a dairy farm in Heilongjiang, China. Inflammatory milk fat globule membrane proteins were detected using ELISA kits, and a fully auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Remarkably, AGP1 has been reported to act as an anti-inflammatory protein 23 , thus being crucial for maintaining immune tolerance. Moreover, it has been reported that both AHSG and AGP1 were reduced before the onset of ketosis in dairy cows 24 . Considering that dairy cows are prone to develop (subclinical) ketosis during the early PP phase, reduced abundance of AHSG and AGP1 in our study is in line with this report.…”
Section: Discussionmentioning
confidence: 93%
“…Remarkably, AGP1 has been reported to act as an anti-inflammatory protein 23 , thus being crucial for maintaining immune tolerance. Moreover, it has been reported that both AHSG and AGP1 were reduced before the onset of ketosis in dairy cows 24 . Considering that dairy cows are prone to develop (subclinical) ketosis during the early PP phase, reduced abundance of AHSG and AGP1 in our study is in line with this report.…”
Section: Discussionmentioning
confidence: 93%
“…Among the overlapping genes, TNFAIP8L2 , MPEG1 , FCRL4 , BOLA‐DQA5 , BOLA‐DQB and HIF1AN genes are associated with vital aspects of the immune system (Bayly‐Jones et al., 2020; Cancro & Tomayko, 2021; Fukunaga et al., 2020; Li et al., 2018; Tang et al., 2023). Moreover, genes related to reproduction ( OSBP2 , BRWD1 and GOLGA4 ; Chu et al., 2012; Ortega et al., 2016; Sigdel et al., 2020), carcass traits ( SCD ; Gao et al., 2022), muscle growth ( IGF2 , GBP4 , ADPRHL1 , NRG2 , TCF12 and TMOD4 ; Abdillah et al., 2022; Adrain, 2020; Cao et al., 2018; Goodall & Schmutz, 2007; Sun et al., 2022; Zhang et al., 2023), high‐altitude adaptation ( CLCA2 ; Terefe et al., 2022) and milk composition ( ORM1 and CSF1 ; Feng et al., 2023; Gao et al., 2017) were also identified (Figures 4a and 5a; Table 1; Tables S5–S10).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of reproductive‐related genes associated with longevity pathways in Kashmir cattle emphasizes their genetic adaptation and robust reproductive success. Additionally, the identification of the ORM1 (Gao et al., 2017), MRPS30 (Illa et al., 2021) and CSF1 (Feng et al., 2023) genes as strong signaling genes relevant to milk composition further highlights their potential role in shaping milk quality attributes in Kashmir cattle.…”
Section: Discussionmentioning
confidence: 99%